MEMBENDUNG ARUS PAHAM KEAGAMAAN RADIKAL DI KALANGAN MAHASISWA PTKIN - Toto Suharto; Ja'far Assagaf (AL-TAHRIR, 2014)
Surakarta, central Java, witnesses proliferation of Islamic radical groups. Many expect that IAIN Surakarta becomes the strongest bulwark in the city to halt the growth of radicalism. Since 2006/2007, Faculty of Education and Teaching at IAIN Surakarta has adopted a program of Integral Muslim Personality Development Supervision written in a book. This program is potentially used to counter-attack the radical ideology. However, the question arises as to whether the content and curriculum of the program express moderate views of Islam or, even, contrarily spread the seed of radicalism. Using a content analysis, this study examines this program. This study find that a number of materials and references of the book in this program are inspired by and derived from Tarbiyah movement, and therefore it fails to be a counter discourse of radicalism for the students in this department. Even a closer look at into the curriculum and the content of the booklet reveals that the program adopts the Tarbiyah Movement methods and mentoring programs such as halaqa, usroh, mantuba and mutaba’ah. The program is thus not promising to serve  an effective means to wage a war against radicalism; it apparantly becomes a firt step toward seeding the Tarbiyah ideology.         Keywords: counter radicalism, education curriculum, P2KMI program